Paying for cost-effective health care: Does it violate both static- and dynamic efficiency? - Tomas J Philipson (University of Oslo, 2015)
Recent research has questioned the rationales of using cost-effectiveness metrics of medical technologies to guide reimbursement. I discuss here the underlying ideas of this research, which argues that reimbursement based on cost effectiveness criteria leads to both static- and dynamic inefficiencies.